Faktor Perceraian Suami Perantau Dalam Perspektif Hukum Keluarga - Rasyidin & Mayang Diwana (Hukum Keluarga Islam IAIN LANGSA, 2021)
In Islam divorce is something that is not prohibited but is an act that is hated by Allah SWT. In Islam itself, the law of divorce is makhruh. Especially in the Sawit Seberang community, divorce has occurred a lot, especially for migrant workers, so that a divorce that occurs in the community is no longer an unusual thing, because there are many factors that trigger divorce in the household. The purpose of this study is to find out what is the biggest factor that triggers so many divorce cases among the community, especially the Sawit Seberang community from among the husbands of immigrants. This research method uses qualitative research methods (field research). The primary data sources were obtained through observation and interviews with the community and the parties concerned who clearly knew about the divorce case. based on the results of research that has been carried out by the author, the author concludes that the dominant factor in the occurrence of divorce among nomad husbands in Sawit Seberang District is the infidelity factor. It can be concluded that the existence of a third party is something that is very influential in household resilience, and this often happens, especially in the Sawit Seberang community.